Perioperative, functional, and oncologic outcomes after ablation or partial nephrectomy for solitary renal tumors: a systematic review and meta-analysis of comparative trials - Wen, Zhi; Wang, Li; Huang, Jing; Liu, Yang; Chen, Cai-xia; Wang, Chong-jian; Chen, Lin-lin; Yang, Xue-song (Frontiers in Oncology, 2023)
Objectives: The perioperative, functional, and oncological outcomes of patients with solitary small renal tumors(SRMs) treated with ablation(AT) or partial nephrectomy(PN) remain controversial. The aim of this study was to compare the outcomes of these two surgical techniques. Methods: In April 2023, we conducted a literature search in several widely used databases worldwide, including PubMed, Embase, and Google Scholar. Review Manager was used to compare various parameters. The study was registered with PROSPERO (CRD42023 411427). Results: Our final meta-analysis included 13 cohort studies with a total of 2,107 patients. Compared to partial nephrectomy (PN), ablation (AT) had shorter hospital stays (WMD -2.37 days, 95% CI -3.05 to -1.69; p < 0.00001), shorter operating times (WMD -57.06 min, 95% CI -88.92 to -25.19; p = 0.0004), less postoperative creatinine increases (WMD -0.17 mg/dL, 95% CI -0.29 to -0.05; p = 0.006), less postoperative glomerular filtration rate decreases (WMD -9.84 mL/min/1.73 m2, 95% CI -14.25 to -5.44; p < 0.0001), less postoperative new-onset chronic kidney disease (OR 0.33, 95% CI 0.16 to 0.71; p = 0.005), and less intraoperative blood loss (WMD -285.92 ml, 95% CI -428.44 to -143.40; p < 0.0001). The transfusion rate was lower in the ablation group (OR 0.17, 95% CI 0.06 to 0.51; p = 0.001). The risk of local recurrence was higher in the ablation group (OR 2.96, 95% CI 1.27 to 6.89; p = 0.01), while the risk of distant metastasis was higher in the partial nephrectomy group (OR 2.81, 95% CI 1.28 to 6.18; p = 0.01). The intraoperative and postoperative complication rates were lower in the ablation group (OR 0.23, 95% CI 0.08 to 0.62; p = 0.004 and OR 0.21, 95% CI 0.11 to 0.38; p < 0.00001, respectively). However, overall survival (1 year, 3 years, 5 years), postoperative dialysis rate, and tumor-specific survival (1 year, 3 years, 5 years) were not different between the two groups.